Detection of triclabendazole and three metabolites in bovine muscle samples with a gold nanoparticle-based lateral flow immunoassay. Issue 42 (18th October 2019) - Wang, Zhongxing; Wu, Xiaoling; Xu, Liguang; Kuang, Hua; Xu, Chuanlai
Abstract : A highly sensitive mAb against TCD was produced by using a novel hapten, and basing on this mAb, a lateral flow immunoassay was developed for the rapid screening of TCD and its metabolites in foodstuff. Abstract : In this study, a highly sensitive monoclonal antibody (mAb) against triclabendazole (TCD) and its metabolites was produced by using a novel hapten. The subclass of this mAb was IgG2a, its IC50 values were 1.49–3.58 ng mL −1 against TCD and its metabolites, and its affinity constant was 5.46 × 10 9 mol L −1 . We then went on to develop a mAb-based lateral flow immunoassay (LFIA) for the rapid screening of TCD and its metabolites in foodstuff using gold nanoparticles as a label. The LFIA-based test strip was assembled using routine procedures. All of the following parameters were optimized including the pH, minimum antibody concentration needed for the synthesis of the AuNP–mAb conjugate, the best coating antigen and its concentration, the volume of the mAb–AuNP conjugate and optimal diluent buffer constituents. Under optimized conditions, the cutoff values for the LFIA were 10 μg kg −1 for TCD, TCD-SO and TCD-SO2, and 25 μg kg −1 for Keto-TCD, and the limits of detection (LODs) were 0.11 μg kg −1 for TCD, 0.28 μg kg −1 for TCD-SO, 0.38 μg kg −1 for TCD-SO2, and 0.47 μg kg −1 for Keto-TCD. The ranges of quantitative detection were 0.22–5.41 μg kg −1 for TCD, 0.56–5.74 μg kg −1 for TCD-SO, 0.76–9.11 μg kg −1 for TCD-SO2, and 0.94–24.02 μg kg −1 for Keto-TCD, respectively. Finally, the assay was further applied to detect TCD and its metabolites in real samples and we are satisfied that this AuNP-based LFIA is a useful tool for the rapid and sensitive screening of TCD medicines in foodstuff samples.